2006
DOI: 10.1177/095207670602100106
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Psychological Contract Fulfilment and Public Service Motivation on Organizational Commitment in the French Civil Service

Abstract: In a context where French public organizations are confronted with a rise in the demandfor high-quality services, with limitedfinancial resources and with a newform ofmanagement based upon a 'results culture', understanding work commitment in the civil service seems to be more crucial than ever

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
113
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(129 citation statements)
references
References 37 publications
8
113
0
8
Order By: Relevance
“…Vincent's levels of AOC, on the other hand, of the perception of fulfillment of the obligations of the employer in the psychological contract and of job performance decreased. These findings offer support to and illustrate findings of previous studies (Cassar & Briner, 2011;Castaing, 2006;Lapointe et al, 2013;Meyer et al, 2002;Parzefall, 2008;Shahnawaz & Goswami, 2011;Simosi, 2013).…”
Section: Psychological Contract Aoc and Job Performancesupporting
confidence: 80%
See 1 more Smart Citation
“…Vincent's levels of AOC, on the other hand, of the perception of fulfillment of the obligations of the employer in the psychological contract and of job performance decreased. These findings offer support to and illustrate findings of previous studies (Cassar & Briner, 2011;Castaing, 2006;Lapointe et al, 2013;Meyer et al, 2002;Parzefall, 2008;Shahnawaz & Goswami, 2011;Simosi, 2013).…”
Section: Psychological Contract Aoc and Job Performancesupporting
confidence: 80%
“…The fulfillment of a psychological contract, on the other hand, was found to have a positive impact on AOC of public sector employees (Parzefall, 2008). In a study of civil servants in France, Castaing (2006) found a significant association between psychological contract variables and AOC.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In particular, the items of the dimension of attraction to policy making lack face and content validity (Camilleri 2006;Coursey and Pandey 2007;Coursey et al 2008;Kim 2009b;Ritz 2011). Others have suggested that commitment to public interest dimension needs to concentrate more on a personal disposition to pursue public values (Castaing 2006;Leisink and Steijn 2009;Taylor 2007), and the items of compassion do not always represent affective motives (DeHart-Davis, Marlowe, and Pandey 2006;Moynihan and Pandey 2007;Wright 2008).…”
Section: Refining the Multidimensional Psm Frameworkmentioning
confidence: 99%
“…Given that the most commonly used measures of PSM were developed in the United States, it is not surprising that scholars have questioned the appropriateness of these measures for explaining and predicting public service-related motivations and behavior internationally (Cerase and Farinella 2009;Coursey and Pandey 2007;Giauque et al 2011;Ritz and Waldner 2011;Vandenabeele 2008b;Wise 2000). Still others have noted a general need to develop a more appropriate measure of PSM that can be used consistently and confidently regardless of the context or culture in which it is studied (Castaing 2006;Leisink and Steijn 2009;Liu, Tang, and Zhu 2008;Taylor 2007;Vandenabeele 2008a;Wright 2008;Wright and Pandey 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A different stream of research has focused on the relationship between PSM and work outcomes, from attitudes such as job satisfaction and organizational commitment, to individual performance and organizational performance Castaing 2006;Kim 2005;Naff & Crum 1999;Vandenabeele 2009). It is this latter research stream that this chapter speaks to, focusing on performance.…”
Section: Public Service Motivation: Institution-embedded Motivationmentioning
confidence: 99%